Transcultural interaction in health services - Camillo da Silva, Elaine Cristina; De Paula Ramos, Dalton Luiz (Acta Bioethica, 2010)
This study had the following objectives: to understand the interaction processes among health professionals and foreign users in the Unidades Básicas de Saúde (UBS) and the Program for Family Health (PSF); to get to know the significance of the health professional’s experience as they interact with foreign users; to put in evidence bioetiques issues in the experience of professionals and foreign users interaction. It was used as a theorical referential the Symbolic Interacionism and as methodological reference a Grounded Theory up to an axial coding. Data analysis presented as conceptual ordering, lead to the definition of four great issues: (1) "trying to communicate"; (2) "detecting limits"; (3) "recognizing interaction as a process"; (4) "recognizing different perspectives". The route of professional – foreign users interaction was developed from one choice: attend everyone (indiscriminately) making approximation possible. To recognize or fail to recognize in the foreign user the dignity of human person seems to be the determining factor for the openness of the professional to the interaction, in his disposition to seek strategies.